KEGIATAN EDUKASI BAHAYA NAPZA BAGI KESEHATAN DAN PERKEMBANGAN INTELEKTUAL ANAK USIA SEKOLAH - Handayani, Kurnia Maidarmi; Sari, Widia; Khudri, Ghaniyyatul; Maribeth, Annisa Lidra (Universitas Mataram, 2024)
Drug abuse poses a significant threat to the future of the younger generation, encompassing narcotics, alcohol, psychotropic substances, and other addictive substances collectively referred to as NAPZA. Recent data from the United Nations Office on Drugs and Crime (UNODC) World Drug Report for 2023 indicates a consistent rise in drug abuse cases globally, with approximately 5.8% of individuals aged 15 to 64 reported to be involved in drug abuse. According to data from Badan Narkotika Nasional (BNN) in 2021, the village of Korong Gadang, situated in the Kuranji District of Padang City, West Sumatra, is classified as an area characterized by a drug abuse alert status. Addressing this issue is paramount, necessitating effective solutions to prevent drug abuse in this locality. One method to accomplish this is by conducting campaigns with groups of school-aged children, the nation's future, regarding drugs and their dangers.The objective of this project is to impart knowledge and educate children of school age concerning drugs and its dangers. Counseling is conducted via lecture by distributing educational materials pertaining to substances and their associated risks. In addition, pre-tests and post-tests were given prior and following to the lecture. The outcomes of this activity demonstrated that the counseling given could increase participants' awareness of drugs and their risks. As a result, counseling can be used as a viable strategy to prevent the distribution of narcotics, particularly among children of school age.